2017
DOI: 10.1007/s13762-017-1594-6
|View full text |Cite
|
Sign up to set email alerts
|

Coupled physicochemical and bacterial reduction mechanisms for passive remediation of sulfate- and metal-rich acid mine drainage

Abstract: Treatment of acid mine drainage (AMD) highly rich in sulfate and multiple metal elements has been investigated in a continuous flow column experiment using organic and inorganic reactive media. Treatment substrates that composed of spent mushroom compost (SMC), limestone, activated sludge and woodchips were incorporated into bacterial sulfate reduction (BSR) treatment for AMD. SMC greatly assisted the removals of sulfate and metals and acted as essential carbon source for sulfate-reducing bacteria (SRB). Alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…8,9 SRB is very important in the biogeochemical cycle of the sulfur and microbial desulfurization process. Muhammad et al 10 found that SRB could remove SO 4 2− and heavy metal ions synchronously. Among them, the fixation rate of iron, copper, lead, and other heavy metal ions is 87∼100%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 SRB is very important in the biogeochemical cycle of the sulfur and microbial desulfurization process. Muhammad et al 10 found that SRB could remove SO 4 2− and heavy metal ions synchronously. Among them, the fixation rate of iron, copper, lead, and other heavy metal ions is 87∼100%.…”
Section: Introductionmentioning
confidence: 99%
“…It can use sodium lactate, ethanol, H 2 , and other electron donors to reduce SO 4 2– under anaerobic (or anoxic) conditions, produce sulfide (including S 2– , HS – , and H 2 S) to precipitate heavy metals, and produce alkali substances to improve pH. , SRB is very important in the biogeochemical cycle of the sulfur and microbial desulfurization process. Muhammad et al found that SRB could remove SO 4 2– and heavy metal ions synchronously. Among them, the fixation rate of iron, copper, lead, and other heavy metal ions is 87∼100% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the microbial treatment of AMD, sulfate-reducing bacteria (SRB) as the representative organisms has caused extensive research and application 5 . Muhammad et al 6 showed that under suitable conditions, SRB could survive in the environment containing sulfate and various metal ions, and the reduction reaction could reduce 87–100% of iron, lead, copper, zinc and aluminum. Sahinkaya et al 7 found that the final sulfate reduction rate could reach 90% in a sulfate-reducing MBR reactor when SRB was inoculated into wastewater with a sulfate concentration of 2000 mg/L and a COD/sulfate of 0.75.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of SRB to extreme conditions and the fact that sulphide reacts with several metals forming precipitates have made these microorganisms known for their potential in bioprocesses to treat waters contaminated with metals and sulphate, such as acid mine drainage (AMD) (e.g. Costa et al 2017;Dev et al 2017;Miran et al 2017;Muhammad et al 2017). However, these waters are usually poor in compounds used by SRB as carbon sources and electron donors to obtain energy, thus their biological treatment requires addition of such products (e.g.…”
Section: Introductionmentioning
confidence: 99%